10PCirculating miR-652-3p as a biomarker of drug resistance in metastatic colorectal cancer patients. (7th November 2019) - Hedayat, S; Lampis, A; Vlachogiannis, G; Khan, K; Cunningham, D; Marchetti, S; Fassan, M; Begum, R; Schirripa, M; Loupakis, F; Valeri, N
Abstract: Background: MicroRNAs (miRs) are small non-coding RNAs involved in cell homeostasis, carcinogenesis and control multiple oncogenic pathways. Numerous miRs deregulation is associated with clinical outcome. Chemo-refractory metastatic CRC (mCRC) patients are often treated with regorafenib. Given the limited clinical benefits of regorafenib in unselected patient populations, there is an unmet need for better patient selection and identification of mechanisms of resistance. Here we aimed to identify circulatory miRs that might be exploited for the upfront selection of patients' to regorafenib treatment. Methods: We ran a translational phase II trial of regorafenib in chemo-refractory mCRC patients. Serum, plasma and tissue biopsies were obtained at baseline (BL), every four weeks and at disease progression (PD). Patient Derived Organoids (PDOs) and PDO-xenotransplants were generated to study primary and acquired resistance to regorafenib. MiR profiling was performed by NanoString nCounter platform of 800 genes and validated with digital droplet (dd)PCR in serum, plasma, PDOs and by In Situ Hybridization (ISH) in matching tissue biopsies. Progression Free Survival (PFS) and Overall Survival (OS) was measured. Further validation was performed in 97 patients from an independent patient's cohort. Results: MiR expression was tested in 43 BL sera and dysregulation in 28 miRs was associated with PFS and OS. Up-regulation of miR-652-3p was associated with worse PFS and OS. These results were validated by ddPCR on the same serum samples, and matching plasmas. ISH confirmed upregulation of this miR in sequential tissues biopsies, PDOs and PDO-xenotransplants of patients with primary and acquired resistance to regorafenib. Validation in an independent patient's cohort confirmed direct association of miR-652-3p dysregulation with OS. Functional experiments to define miR652-3p mediated resistance have shown that there is a decrease of tumour growth and migration in miR-652-3p inhibition in cell lines and PDOs. Conclusions: We provided initial evidence suggesting that circulating miR-652-3p might work as a predictive biomarker for the upfront selection of patients' candidate to regorafenib treatment. Legal entity responsible for the study: Academic. Funding: Royal Marsden. Disclosure: All authors have declared no conflicts of interest.